ANALYSIS OF LEGAL PROTECTION FOR CONSUMERS PURCHASING APARTMENTS IN THE INDONESIAN LEGAL SYSTEM - Sudibyo, Herry (Reflektika, 2025)
The development of the property industry, particularly apartments, presents opportunities and challenges regarding consumer legal protection. Consumers who purchase apartment units often face issues related to information transparency, unclear agreements, delays in handover, and substandard building quality. This study aims to analyse legal protection for apartment buyers in the Indonesian legal system through legislative instruments such as the Consumer Protection Law, the Civil Code, and specific regulations on housing and residential areas. The research method used is a normative juridical approach that examines positive legal provisions, doctrines, and judicial practices. The study results show that legal protection for apartment buyers has been regulated in a normative manner. However, its implementation still faces various obstacles, especially regarding law enforcement and the certainty of consumer rights. Therefore, it is necessary to strengthen regulations, increase government supervision, and raise legal awareness among business actors to uphold the principles of justice, certainty, and consumer benefits.